Globalization, the strong state and education policy: the politics of policy in Asia. Issue 6 (1st November 2016) - Lim, Leonel
Abstract: Much of the scholarship around the workings of education policy has focused on the global West and has taken for granted the state's limited abilities in the control of policies as both text and discourse. Drawing upon policy texts from the Singapore Ministry of Education and ethnographic data collected in a Singapore school, this paper explores the enlarged but by no means unproblematic role of strong states and their provision and regulation of education policy in Asia. The paper begins by providing an overview of the major emphases and research trajectories taken up by the field of education policy. This is followed by an elaborated account of the nature and politics of the strong state in Asia in general and particularly in Singapore. These theoretical and contextual remarks then pave the way for a closer look at how the Singapore state functions as a major mediator and recontextualizing agent of education policy. The discussion foregrounds the enlarged role of the state in prescribing, translating, and regulating how a national curriculum policy on critical thinking finds its way into the practice of local schools and classrooms. The paper concludes with a number of remarks on the deparochialization of research and how recent work on 'Asia as method' may provide a fortuitous approach to critiquing hegemonic systems of knowledge production.